Couchsurfing involvement in non-profit peer-to-peer accommodations and its impact on destination image, familiarity, and behavioral intentions. (September 2020) - Kuhzady, Salar; Çakici, Celil; Olya, Hossein; Mohajer, Boshra; Han, Heesup
Abstract: Accommodation is a fundamental part of tourism, and it plays an important role in the tourist experience. The emerging economy and especially the peer-to-peer accommodations (P2P) have shaken up the conventional accommodations sector. While most P2P accommodation studies have focused on the monetary platform, which includes Airbnb, there is little knowledge about the linkages of involvement and behavioral intentions on the non-profit accommodation users. This empirical study applied a multiple-methods approach to investigate the positive impacts of involvement on couchsurfing, such as P2P accommodations on the destination image, familiarity, and the behavioral intentions. The data was collected from 609 travelers who have used couchsurfing while traveling to Turkey from 2016 to 2017. The results revealed that involvement in couchsurfing improved the destination image, familiarity, the E-WoM, and the revisit intention of couchsurfers. This study also discusses the practical implications.